Risk assessment in systemic lupus erythematosus-associated pulmonary arterial hypertension: CSTAR-PAH cohort study - Qian Wang; Junyan Qian; Mengtao Li; Xiao Zhang; Wei Wei; Xiaoxia Zuo; Ping Zhu; Shuang Ye; Wei Zhang; Yi Zheng; Wufang Qi; Yang Li; et al. (SAGE Publishing, 2022)
Objective: This study evaluated the prognostic value of the multivariable risk assessment for systemic lupus erythematosus (SLE)-associated pulmonary arterial hypertension (PAH). Methods: A multicenter prospective cohort of SLE-associated PAH (CSTAR-PAH cohort) diagnosed based on right heart catheterization (RHC) was established. Baseline and follow-up records were collected. Three methods of risk assessment, including (1) the number of low-risk criteria, based on World Health Organization functional class (WHO FC), 6-min walking distance (6MWD), right atrial pressure (RAP), and cardiac index (CI); (2) the three-strata stratification based on the average risk score of four variables (WHO FC, 6MWD, RAP, and CI); and (3) the four-strata stratification based on COMPARE 2.0 model were applied. A risk-assessment method using three noninvasive low-risk criteria was applied at the first follow-up visit. Survival curves between patients with different risk groups were compared by Kaplan-Meier's estimation and log-rank test. Results: Three-hundred and ten patients were enrolled from 14 PAH centers. All methods of stratification at baseline and first follow-up significantly discriminated long-term survival. Survival rates were also significantly different based on the noninvasive risk assessment in first follow-up visit. Survival deteriorated with the escalation of risk from baseline to first follow-up. Patients with baseline serositis had a higher rate of risk improvement in their follow-up. Conclusion: The risk assessment has a significant prognostic value at both the baseline and first follow-up assessment of SLE-associated PAH. A noninvasive risk assessment can also be useful when RHC is not available during follow-up. Baseline serositis may be a predictor of good treatment response in patients with SLE-associated PAH.